2011
DOI: 10.3109/08820538.2011.577498
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell Therapies for Geographic Atrophy of Age-Related Macular Degeneration

Abstract: There is currently no FDA-approved therapy for treating patients with geographic atrophy (GA), a late stage of age-related macular degeneration (AMD). Cell transplantation has the potential to restore vision in these patients. This review discusses how recent advancement in induced pluripotent stem (iPS) cells provides a promising therapy for GA treatment. Recent advances in stem cell biology have demonstrated that it is possible to derive iPS cells from human somatic cells by introducing reprogramming factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 93 publications
0
17
0
1
Order By: Relevance
“…The poor outcomes have several explanations: (1) the invasive surgery required to prepare the subretinal space; (2) late-stage disease is associated with marked loss of RPE and photoreceptors; (3) a change in myeloid activation and glia activation in the aging retina, or (4) the source of RPE (i.e., advanced donor age) 31, 34. To overcome some of these problems, human embryonic stem cells (hESCs) or induced pluripotent stem cell (iPSC)-derived RPE cells have been used for subretinal transplantation 33, 35, 36. Studies have reported success with both hESC- and iPSC-derived RPE in restoring vision in animal models,35, 36 but although these RPE cell transplants in humans do not result in rejection or hyperproliferation, vision was not greatly enhanced post-transplantation 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor outcomes have several explanations: (1) the invasive surgery required to prepare the subretinal space; (2) late-stage disease is associated with marked loss of RPE and photoreceptors; (3) a change in myeloid activation and glia activation in the aging retina, or (4) the source of RPE (i.e., advanced donor age) 31, 34. To overcome some of these problems, human embryonic stem cells (hESCs) or induced pluripotent stem cell (iPSC)-derived RPE cells have been used for subretinal transplantation 33, 35, 36. Studies have reported success with both hESC- and iPSC-derived RPE in restoring vision in animal models,35, 36 but although these RPE cell transplants in humans do not result in rejection or hyperproliferation, vision was not greatly enhanced post-transplantation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome some of these problems, human embryonic stem cells (hESCs) or induced pluripotent stem cell (iPSC)-derived RPE cells have been used for subretinal transplantation 33, 35, 36. Studies have reported success with both hESC- and iPSC-derived RPE in restoring vision in animal models,35, 36 but although these RPE cell transplants in humans do not result in rejection or hyperproliferation, vision was not greatly enhanced post-transplantation 35 . Although extremely promising, concerns remain regarding genetic stability, and this approach does not overcome the necessity to invade the subretinal space or limitations in disseminating cells across the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…A subpopulation of Muller glia with progenitor gene expression have been identified in rodents but there is no definitive evidence that they produce differentiated and functional neurons even though they can express markers for bipolar cells and photoreceptors after injury (Ooto et al, 2004). The clinical approach has been to attempt transplantation of autologous RPE cells or RPE-like cells derived from embryonic stem cells (ESCs) or induced pluripotent stem cells (iPS) (Carr et al, 2009; Du et al, 2011; Lu et al, 2009; Vugler et al, 2007). Human ESC or iPS have the potential to differentiate into rods and cones (Bi et al, 2009; Ikeda et al, 2005; Osakada et al, 2009; Osakada et al, 2007) and can restore light responses when transplanted into the retina of Crx-deficient mice (Lamba et al, 2009a).…”
Section: Preventing or Reversing Oxidative Damage In The Retinamentioning
confidence: 99%
“…To overcome this problem, new therapies such as RPE cell transplantation and transplantation of stem cells are being tried. 3,4 Macular translocation surgery has also been used to treat AMD. In this surgery, the macular area is moved from the underlying damaged RPE to an area of healthier RPE.…”
Section: Introductionmentioning
confidence: 99%